(untitled) (Damu Journal of Sport Sciences, 2025)
The study aims to identify the effect of concurrent training on lactic endurance and agility in under-19 soccer players. The researchers adopted an experimental approach with a two-group equivalent design with pre-test and post-test as the basis for implementation, due to its suitability to the nature of the research problem. The researcher deliberately identified the research community as football players from Karbala Sports Club, aged under (19 years), totaling (23) players for the 2023-2024 training season. The training included (24) training sessions. The duration of the training sessions ranged from (30-40 minutes) with the main part of the training session lasting from (85-90 minutes). The researcher observed the principle of undulation in the training load. Magnesium lactate was administered twice daily according to medical advice. The intensity of the exercises ranged from (60%-100%) of the maximum load the player could tolerate. The researchers concluded that magnesium lactate has a significant impact on preventing cramps and injuries resulting from high muscle tension in players, as it is a recovery supplement. Synchronized training has a positive impact on developing agility.